Minimally invasive wireless motility capsule to study canine gastrointestinal motility and pH. (September 2017) - Warrit, K.; Boscan, P.; Ferguson, L.E.; Bradley, A.M.; Dowers, K.L.; Rao, S.; Twedt, D.C.
Highlights: The wireless motility capsule was tolerated by all dogs while at home. It provided data from the different sections of the gastrointestinal tract (GIT). A minimally invasive tool to assess GIT solid phase transit times, pressures and pH. Smaller dog size may represent a limitation. Abstract: The aim of this study was to describe the feasibility of using a gastrointestinal tract wireless motility capsule (WMC) that measured intraluminal pressure, pH and transit time through the gastrointestinal tract, in dogs in their home environment. Forty-four adult healthy dogs, eating a standard diet, were prospectively enrolled. The WMC was well tolerated by all dogs and provided data from the different sections of the gastrointestinal tract. Median gastric emptying time was 20 h (range, 6.3–119 h), demonstrating a large range. The gastric pressure pattern and pH depended on the phase of food consumption. The small bowel transit time was 3.1 h (range, 1.6–5.4 h) with average contraction pressures of 6.5 mmHg (range, 1.1–21.4 mmHg) and pH 7.8 (range, 7–8.9). The large bowel transit time was 21 h (range, 1–69 h) with average contractions pressures of 0.9 mmHg (range, 0.3–2.7 mmHg) and pH 6.4 (range, 5.3–8.2). There was considerable individual variation in motility patterns and transit times between dogs. No difference was observed between the sexes. No relationships between any transit time, bowel pH or pressure pattern and bodyweights were identified. The WMC likely represents movement of a large non-digestible particle rather than normal ingesta. Due to its large size, the WMC should not be use in smaller dogs. The WMC is a promising minimally invasive tool to assess GIT solid phase transit times, pressures and pH. However, further studies are necessary due to the current limitations observed.